Results of the Puti-Platt Operation for Recurrent Anterior Dislocation of the Shoulder (Journal of Science Foundation, 2013)
This was a prospective clinical trial carried out at NITOR, Dhaka from July 2004 to June 2006 involving 18 patients with recurrent anterior dislocation of the shoulder. All the cases were managed by Putti-Platt operative procedure. The aim of this study was to evaluate the effectiveness of the Putti-Platt procedure in the management of recurrent anterior dislocation of the shoulder. In this study, purposing sampling methods were followed irrespective of sex. Most common age group in this series was 21-30 years. This prospective clinical study comprised with 18 patients, 16 cases (88.88%) showed excellent and good results and 2 cases (11.11%) showed fair results. Therefore, Putti-Platt procedure can be considered as an effective procedure in the treatment of recurrent anterior dislocation of shoulder. Less tissue handling, close postoperative follow-up and active muscle exercise is essential for producing good result. The long-term result is beyond the scope of this study. Long-term follow up is needed to evaluate the final out come of these patients. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14647 J. Sci. Foundation, 9(1&2): 51-57, June-December 2011